Refractive Status in Eyes Implanted with Toric and Nontoric Intraocular Lenses during Combined Cataract Surgery and Microhook Ab Interno Trabeculotomy - Yasuyuki Takai; Kazunobu Sugihara; Mihoko Mochiji; Kaoru Manabe; Aika Tsutsui; Masaki Tanito (Journal of Ophthalmology)
Purpose. To compare the refractive status between eyes implanted with toric and nontoric intraocular lenses (IOLs) during combined cataract surgery and microhook ab interno trabeculotomy (μLOT), a minimally invasive glaucoma surgery (MIGS). Methods. Twenty eyes of 20 patients who had open-angle glaucoma, cataract, and preexisting regular corneal astigmatism exceeding 1.5 diopters (D) and underwent combined μLOT and phacoemulsification were recruited retrospectively. Ten eyes were implanted with a toric IOL and 10 eyes with a nontoric IOL. The primary outcomes were the uncorrected visual acuity (UCVA) and refractive cylinder at 3 months postoperatively. Results. The mean UCVA of the toric IOL group (logarithm of the minimum angle of resolution (logMAR), 0.23 ± 0.25) was significantly better than that of the nontoric IOL group (logMAR, 0.45 ± 0.26) at 3 months postoperatively (p<0.05). The mean absolute residual refractive cylinder of the nontoric IOL group (2.25 ± 0.62 D) was significantly greater than that of the toric IOL group (1.30 ± 0.68 D) (p<0.05). Postoperatively, 60% of eyes in the toric IOL group and 10% in the nontoric IOL group had an absolute refractive astigmatism level of 1.5 D or less. Surgically induced astigmatism (0.77 ± 0.43 D for toric group and 0.60 ± 0.32 D for nontoric group) and IOP reduction (33.9 ± 15.6% for toric group and 29.4 ± 11.7% for nontoric group) were not different between groups. Conclusions. Use of toric IOL during combined cataract surgery and μLOT is possible and better than not, but physician should prevent their patient of persisting residual astigmatism. The study was registered at https://www.umin.ac.jp/, and the clinical trial accession number is https://clinicaltrials.gov/ct2/show/UMIN000043141.